Development of a Mathematical Model for Optimal Pricing Strategies for Perishable Goods - Yahaya, Ahmad Abubakar; Usman, Abdullahi Mohammed; Hassan, Aisha Sheikh (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
This study introduces a deterministic linear programming (LP) framework aimed at enhancing dynamic pricing strategies for perishable products with predictable demand trends. Since the value of these items declines over time due to spoilage or becoming outdated, pricing decisions must be made carefully and promptly. The proposed model seeks to maximize total revenue within a defined time frame by incorporating constraints related to inventory levels, time-dependent product depreciation, and the relationship between price and demand. In contrast to heuristic or stochastic models, this approach relies on fixed demand forecasts and known deterioration rates, enabling efficient and transparent solutions using conventional LP solvers. A practical example in a retail perishables items illustrates how the model improves profitability while minimizing waste. The results show that increased leads to higher optimal quantities and slightly lower prices to capture demand and the total revenue realized is N94, 500.